Chang'E‐3 spacecraft surface reflection causes turbulence on VLBI delay. Issue 2 (15th February 2017) - He, Qingbao; Liu, Qinghui; Zheng, Xin
Abstract: The third Chinese lunar spacecraft Chang'E‐3 (CE3) was launched in 2013, and very long baseline interferometry (VLBI) observations were performed to improve accuracy of its orbit determination. During all the observation time, VLBI group delay experienced very large turbulence, which was up to hundreds of picoseconds, and with variation period of a few tens of seconds. However, VLBI group delay of another lunar spacecraft Chang'E‐5‐T1 (CE5T1), which was launched in 2014, did not show such turbulence. Influences from the troposphere, ionosphere, ground instruments, and phase characteristics of the on board antennas were considered at first, but none of these were the main cause of this large turbulence. Further investigations were made on differential phase delay turbulence, signal‐to‐noise ratio, and layout of spacecraft. The investigation results indicated that the large turbulence on group delay was caused by an interference of reflected signals from the CE3 spacecraft surface. Simulations proved that the delay error caused by signal reflection varied with frequency and therefore caused large turbulence on group delay. To minimize the multipath effect caused by signal reflection, some possible solutions are presented. Key Points: An interference of reflected signals from spacecraft surface caused large turbulence on Chang'E‐3 group delay Phase delay error caused by signal reflection varied with frequency Spacecraft with simple structure is better for reducing reflected signals into ground telescopes